Records of the Aborigines Advancement League (Victoria) in the Riley Collection - Aborigines Advancement League (Vic.) (1959)
Circulars, correspondence, amendments, proposals, opinion papers.
Acquired as part of the Riley Collection.
Keywords: Aborigines Advancement League (Vic.); Aboriginal Australians -- Victoria